2020
DOI: 10.31925/farmacia.2020.6.13
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities and Phytochemical Screening of Ethanol Extracts From Adonis Paryadrica (Ranunculaceae)

Abstract: In this study, secondary metabolite profiles of flower, leaf and root of Adonis paryadrica ethanolic extracts were performed by using a newly developed and validated LC-MS/MS method. For this purpose, the LC-MS/MS system was used for the quantitative and qualitative analysis of 37 phytochemicals. The main component of the flower, leaf and root extracts was the quinic acid (160, 111 and 64 mg/kg, respectively). Antioxidant activities were determined using methods such as DPPH (SC50, mg/mL), FRAP (µM TEAC), CUPR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…Antioxidant studies of species belonging to the genus Adonis are limited in the literature (Mohadjerani et al, 2014;Ucuncu et al, 2020;Guo et al, 2022). In antioxidant studies of A. paryadrica with only ethanol extracts, researchers used different parts of the plant and obtained effective results on the gallic acid equivalent (Ucuncu et al, 2020). The data obtained from this study also showed that the difference in the extract had an effect on the antioxidant properties of the Trolox equivalent.…”
Section: Antioxidant Activitymentioning
confidence: 66%
See 4 more Smart Citations
“…Antioxidant studies of species belonging to the genus Adonis are limited in the literature (Mohadjerani et al, 2014;Ucuncu et al, 2020;Guo et al, 2022). In antioxidant studies of A. paryadrica with only ethanol extracts, researchers used different parts of the plant and obtained effective results on the gallic acid equivalent (Ucuncu et al, 2020). The data obtained from this study also showed that the difference in the extract had an effect on the antioxidant properties of the Trolox equivalent.…”
Section: Antioxidant Activitymentioning
confidence: 66%
“…Evaluation of the biological activities of valuable natural metabolites of plants is one of the most important research areas today and there are many studies carried out in this field (Cüce et al, 2017(Cüce et al, , 2019Cüce and Basançelebi, 2021;Sarikurkcu et al, 2021). The different techniques and methods used in these studies or the different extraction techniques and solvents for the same species can be shown among the reasons for the results obtained from the studies (Jahanban-Esfahlan et al, 2019;Ucuncu et al, 2020;Sarikurkcu et al, 2020). Due to this situation, the researchers preferred ethanol extracts for A. paryadrica in previous studies and reported that they obtained similar results in terms of total phenolic contents with the data in our study (Ucuncu et al, 2020).…”
Section: Chemical Compositionmentioning
confidence: 99%
See 3 more Smart Citations